‘It was a time for ELSAs to come alive’: exploring experiences of the Emotional Literacy Support Assistant role in the context of the Covid-19 pandemic - Endersby, Katharine (2021)
The Emotional Literacy Support Assistant (ELSA) initiative is designed to develop the skills of Teaching Assistants (TAs) to improve the capacity of schools to support pupils’ social and emotional wellbeing. Existing research has suggested that the ELSA role warrants further exploration, particularly in relation to its parameters, emotional challenges, and the qualities required. Recent research has also recognised the integral role that TAs have played in sustaining school communities throughout the Covid-19 pandemic and has called for a focus on TAs’ voices and experiences. The present study, therefore, aims to address the gap highlighted in existing research by exploring experiences of the ELSA role in the context of the Covid-19 pandemic.